Rationale for the priority of the property mobility indicator in the assessment process and asset management of commercial organizations - M. V. Galazova (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. Among the many ﬁnancial indicators for assessing the condition of assets, it is important to highlight the indicator of property mobility, which determines the share of tangible assets in their total value.Goal. The purpose of the study is to substantiate the alternativeness of the property mobility indicator in the process of assessing and managing corporate assets.Materials and methods. During the research, the works of Russian authors characterizing the state of assets of commercial organizations were studied, showing that most of the authors pay special attention to the coeﬃcient of ﬁnancial autonomy and its criterion level. Others is determine the indicator of property mobility as part of the analysis of the ﬁnancial and economic activities of a commercial organization; not all economists indicate its criterion level.Results and discussion. The work in the theoretical ﬁeld of research substantiates that an increase in immobilized assets is accompanied by the appearance of non-working capital, which negatively aﬀects the return on assets, and the growth of mobile productive assets ensures the liquidity of the organization in the long term. In the theoretical and methodological aspect, the attitude towards the mobility of property of diﬀerent economic agents has been studied. In the practical area of research, a comparison of the values of the property mobility indicator in large, medium-sized and small organizations indicates that property in large and medium-sized organizations is more mobile (the share of mobile assets in total varies between 68,1–77,4 %) than in small ones organizations (52–55,4 %), etc.Conclusion. As a result, the theoretical and practical signiﬁcance of the property mobility indicator is substantiated. Its value should be at least 50 %, which will support both liquidity and return on assets at the current moment and in the future.